2019
DOI: 10.3399/bjgp19x700769
|View full text |Cite
|
Sign up to set email alerts
|

Association between GPs’ suspicion of cancer and patients’ usual consultation pattern in primary care: a cross-sectional study

Abstract: BackgroundPatients who rarely consult a GP in the 19–36 months before a cancer diagnosis have more advanced cancer at diagnosis and a worse prognosis. To ensure more timely diagnosis of cancer, the GP should suspect cancer as early as possible.AimTo investigate the GP’s suspicion of cancer according to the patient with cancer’s usual consultation pattern in general practice.Design and settingA cross-sectional study based on survey data from general practice of 3985 Danish patients diagnosed with cancer from Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…In these cases, the GP may attribute the symptoms of the very worried patients to the patient's usual GP attendance patterns and thereby less often perceive the presented symptoms as potential cancer signs in worried frequent attenders. This finding is in line with the results reported by Jensen et al (2019), who found that the GP was less likely to suspect cancer or serious illness in patients who usually consulted general practice often. This emphasises the importance of better knowledge and clinical focus on these patients.…”
Section: Excising Literature and Interpretation Of Findingssupporting
confidence: 92%
See 1 more Smart Citation
“…In these cases, the GP may attribute the symptoms of the very worried patients to the patient's usual GP attendance patterns and thereby less often perceive the presented symptoms as potential cancer signs in worried frequent attenders. This finding is in line with the results reported by Jensen et al (2019), who found that the GP was less likely to suspect cancer or serious illness in patients who usually consulted general practice often. This emphasises the importance of better knowledge and clinical focus on these patients.…”
Section: Excising Literature and Interpretation Of Findingssupporting
confidence: 92%
“…Cancer types that typically present with vague or unspecific symptoms are less often perceived as suspicious by the GP (Holtedahl et al, 2017; Jensen et al, 2014; Scheel et al, 2013) and thus more often difficult to diagnose (Lyratzopoulos et al, 2014). Moreover, the patient's degree of worry and perceived symptom seriousness, knowledge about symptoms and help‐seeking behaviour have also been linked with patient‐related sociodemographic characteristics, comorbidity and symptomatology in both cancer research as well as in other research fields (Forbes et al, 2014; Hvidberg et al, 2015; McCutchan et al, 2015; Niksic et al, 2015; Salika et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies of this population have shown that customary non‐attending patients seek help at the same point in time and to a similar extent as attending patients in the period just before the cancer disease, that is when the cancer disease can influence the patients' healthcare‐seeking behaviour (Jensen et al, ). However, the GPs are more likely to suspect cancer among the customary non‐attenders when they eventually do show in general practice (Jensen et al, ), which could indicate that these patients are more ill when attending health care. This suggests that the worse cancer prognosis seen in customary non‐attenders is not only caused by the cancer disease itself; it is also influenced by personal and structural factors.…”
Section: Discussionmentioning
confidence: 99%
“…We identified all first‐time cancer patients aged 50–90 years registered from 1 January 2009 to 31 December 2013 in the Danish Cancer Register (DCR) with a cancer coded as C00‐C99 (except C44) according to the International Classification of Diseases, 10th revision (ICD‐10) (Gjerstorff, ). Patients aged under 50 years were not included due to (a) low incidence of cancer before the age of 50, (b) risk of misclassification of women's consultation frequency due to, for example birth control consultations and (c) different assessment made by the GP of these patients (Jensen, Merrild, Møller, & Vedsted, ). Patients were only eligible if they had no previous cancer (except for previous non‐melanoma skin cancer), had a valid personal registration number (PRN), had not lived outside Denmark during the 3 years preceding the diagnosis and were listed with a Danish general practice.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple factors exist that may influence GPs' decision to act upon a patient's symptom presentation, such as different guidelines, pressure to reduce referrals, their own knowledge and skills [9] and time restraints [10]. Furthermore, some researchers suggest that GPs are more likely to suspect cancer in patients who seldom seek primary care [1,11], but also that increased consultation frequency in primary care is a risk marker for cancer [12][13][14]. Additionally, research suggest that GPs use their gut-feeling when suspecting cancer and making decisions about referral to secondary care [15,16].…”
Section: Introductionmentioning
confidence: 99%